Simplified numerical model used in structural analysis of latticed steel structure - Silva, Ricardo da; Porto, Thiago Bonjardim (Revista Hipótese, 2019)
This work had the objective of evaluating the feasibility of the use of simplified processes in the structural analysis of a latticed structure. In the case study presented, it was possible to verify that the support reactions and deformations gave very close results, both when done in a software for three-dimensional analysis using the finite element method, as well as a 2D academic software for bar analysis isotropic properties and homogeneous. The results presented a relative error of 2%, thus demonstrating that the simplified and expeditious analysis allows good results for a conceptual or basic analysis of a structure.
Keywords: FEA; Numerical Modeling; Latticed Steel Structures; Current Transformer Support